Penyakit Crohn: Laporan Kasus - Siwy, Paul V.; Gosal, Fandy (Medical Scope Journal, 2020)
Abstract: Crohn’s disease is an inflammatory transmural bowel disease with unspecific clinical characteritics. It could involve all parts of the digestive system. The exact cause of this disease remains unknown. Its manifestation depends on the location of involved intestinal mucosa, however, it could also occur extra intestinal. We reported a case of Crohn’s disease in a 54-year-old male. In this patient there was defecation with blood in stool, abdominal pain, nausea, and weight loss. Diagnosis was based on history, physical examination, endoscopic examination and colonoscopy, as well as histopathological examination. Colonoscopy EGD examination and tissue biopsy were performed on this patient and revealed esophagitis EGD classification of Los Angeles grade A and erosive gastritis. The results of colonoscopy suggested Crohn’s disease, and internal and external hemorrhoids. Pathology examination showed non-specific chronic gastritis, nonspecific chronic ileitis with datia cells, nonspecific pancolitis, and specific chronic proctitis. Disease activity measured by using CDAI (Crohn Disease Activity Index) score was 170 (mild disease). Moreover, based on the Montreal classification it was classified as A3 L3 B1 and SES-CD (Simple Endoscopic Scoring System in Crohn’s Disease) with value of 0 (not active). This patient was planned to be treated with 500 mg of mesalazine three times daily.Keywords: Crohn’s disease Abstrak: Penyakit Crohn adalah bagian dari penyakit inflamasi saluran cerna dengan karakteristik klinis yang tidak jelas, transmural, dan dapat mengenai semua bagian saluran cerna. Sampai saat ini etiologinya belum diketahui pasti. Manifestasi penyakit ini bervariasi tergantung kerusakan dari lokasi mukosa intestinal yang terkena. Manifestasi ini dapat juga terjadi di luar sistem saluran cerna. Kami melaporkan suatu kasus penyakit Crohn pada seorang laki-laki berusia 54 tahun. Pada pasien ini didapatkan buang air besar disertai darah, nyeri perut, mual dan penurunan berat badan. Diagnosis ditegakkan berdasarkan anamnesis, pemeriksaan fisik, pemeriksaan endoskopi dan kolonoskopi serta pemeriksaan histopatologik. Pemeriksaan EGD-kolonoskopi dan biopsi jarring-an dengan hasil EGD esofagitis klasifikasi Los Angeles grade A dan gastritis erosiva. Hasil kolonoskopi ialah kesan suspek penyakit Crohn dengan hemoroid interna dan eksterna. Hasil histopatologi mendapatkan gastritis kronik non spesifik, ileitis kronik non spesifik dengan sel datia, pankolitis non spesifik dan proktitis kronik non spesifik. Aktivitas penyakit diukur dengan skor CDAI sebesar 170 (aktivitas ringan) dan berdasarkan klasifikasi Montreal diklasifikasikan sebagai A3 L3 B1 dan SES-CD sebesar 0 (tidak aktif). Pasien ini direncanakan untuk diterapi dengan pemberian mesalasin 500mg tiga kali sehari.Kata kunci: penyakit Crohn